2016
DOI: 10.1016/j.cpc.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the manifest left–right symmetric model in FeynRules

Abstract: We present an implementation of the manifest left-right symmetric model in FeynRules. The different aspects of the model are briefly described alongside the corresponding elements of the model file. The model file is validated and can be easily translated to matrix element generators such as MadGraph5_aMC@NLO, CalcHEP, Sherpa, etc. The implementation of the left-right symmetric model is a useful step for studying new physics signals with the data generated at the LHC.Keywords: left-right model; Feynman diagram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…We calculate the W R -production cross section at NLO using the FeynRules [35] implementation of the LRSM [36] in MadGraph [37] with NNPDF2.3 PDF sets [38]. We find σ(pp → W R ) = 223.4 fb for M W R = 1.9 TeV and g R = 0.51.…”
Section: Lhc Phenomenologymentioning
confidence: 99%
“…We calculate the W R -production cross section at NLO using the FeynRules [35] implementation of the LRSM [36] in MadGraph [37] with NNPDF2.3 PDF sets [38]. We find σ(pp → W R ) = 223.4 fb for M W R = 1.9 TeV and g R = 0.51.…”
Section: Lhc Phenomenologymentioning
confidence: 99%
“…Instead it is minimal when the relation In order to see how the above results are affected once hadronization effects are taken into account, we extent the Feynrules implementation of the mLRSM in [46] to include leptonic mixing in the type II see-saw dominance for C as the LR symmetry, where it can be shown that V R = K e V * L . The events at the parton level are simulated with Madgraph 5 [47] and hadronization effects with Pythia 6 [48].…”
Section: Jhep05(2016)176mentioning
confidence: 99%
“…In addition, for the heavy Majorana neutrino coupling to the electron flavor, there are stringent constraints from non-observation of the rare LNV process of neutrinoless double beta decay (0νββ) [88]. Assuming that the purely RH current contribution to 0νββ is the dominant one and using the latest limit from GERDA phase-II on the half-life of 76 Ge, T 0ν 1/2 ≥ 5.3×10…”
Section: Enhanced Sensitivity To Wrmentioning
confidence: 99%
“…(4), calculated using a FeynRules [75] implementation of the L-R seesaw model [76] in MadGraph5 [77], are shown in Fig. 2 for a modest value of center of mass energy √ s = 500 GeV.…”
Section: Comparison Between Unpolarized and Polarized Cross Sectionsmentioning
confidence: 99%